Otras religiones, otras políticas: algunas relaciones entre movimientos sociales y religiones sin organización central = Other religions, other policies : some relationships between social movements and religions without central organization - Carozzi, María Julia (Ciencias sociales y religión, 2006)
The article analyzes relationships that may be established betweendecentralized religions and social movements, based on data drawn from four casestudies. It is argued that an event that triggers both a massive religious response aswell as a corresponding protest movement does not necessarily imply the pre-existenceof veiled protest, as some authors have argued, but sometimes involves a radical re-framing of the situation. It is also suggested that in situations where the threat ofrepression against collective action is high, the goals of a social movement may bemaintained as the means to accomplish them are spiritualized, fueling a religiousmovement. Further, it proposes that religions and social movements that appeal tothe same segments of the population develop similar forms of organization. Finally,it states that active participation in a social movement may transform the meaningsassigned to spiritual beings, re-framing them in its own terms.